Impact of Green Advertising and Packaging on Purchase Decisions via Green Perceived Value - Inggrid; Puspasari, Tri Ratih; Yunus, Ulani (Ilomata International Journal of Social Science, 2024)
This study seeks to explore the impact of green advertising, eco-friendly packaging, and perceived green value on consumer purchasing decisions within the beverage industry, particularly in the bubble tea sector. Most bubble tea beverages are served in disposable plastic cups, lids, and straws, contributing to the accumulation of waste in Indonesia. Observing this issue, the Indonesian public has begun to feel a sense of guilt associated with the use of plastic packaging and prefers brands that incorporate sustainability in their packaging. Consequently, Chatime has initiated the implementation of green marketing by introducing the Eco Cup as an environmentally friendly alternative beverage packaging made from paper. Chatime promotes its Eco Cup to consumers through green advertising on Instagram. This study employs the SOR theory to explain how green advertising and green packaging serve as stimuli that partially influence green perceived value (the organism), ultimately leading to purchase decisions .(the response). Using a quantitative approach with a survey method, questionnaires were distributed to 400 respondents. The findings indicate that while green perceived value has an indirect impact, the direct influence of green advertising and green packaging on purchase decisions is more significant. The indirect effect of green packaging on purchase decisions through green perceived value is notable, as is the direct influence of green packaging on both green perceived value and purchase decisions. Green packaging plays a crucial role in shaping positive perceptions before individuals make a purchase